Agribusiness Development Strategy for Herbal Medicine Products in Makassar City (Case Study of Ash Store) - Ananda Putri; Basri Bado; Abd Rahim; Diah Retno Dwi Hastuti; Citra Ayni Kamaruddin (JURNAL AGRIBISAINS, 2026)
The herbal medicine agribusiness plays an important role in supporting public health through the use of bioactive plants. In Makassar City, Ash Store is one of the herbal medicine businesses that utilizes local raw materials and digital-based marketing. This study aims to identify internal and external conditions and formulate a development strategy for Ash Store's herbal medicine agribusiness in Makassar City. This study uses a qualitative approach with data collection techniques through questionnaires, interviews, observations, and documentation. The SWOT analysis results show that the Ash Store herbal medicine business is in Quadrant I (Growth Oriented Strategy), which indicates that the business conditions are very supportive for development. The recommended development strategy is to maximize internal strengths in the form of unique herbal medicine recipes, guaranteed raw material quality, strong branding, and halal certification to take advantage of digital marketing opportunities, market distribution expansion, and government support for herbal MSMEs to increase business competitiveness and sustainability.